The Actual Problems of Forming of Russia's Potential of Soft Power - G Y Filimonov (RUDN Journal of Political Science, 2012)
The article presents author's vision of Russian cultural influence («soft power») regeneration and further development in the post Soviet Union territory and the rest of the world. Particular attention is paid to the necessity of Russian language learning programs in schools and universities of the CIS countries. There's also emphasis on the need to create a federal agency responsible for development and implementation of Russian public diplomacy, cultural diplomacy, foreign cultural policy, informational and propagandistic maintenance of the foreign policy. The survey also contains analysis of the conditions that are necessary to build up a new model of Russian public diplomacy.